Vocational Teachers Challenges in Developing Their Professional Competence in Indramayu - Indra Yoga Prawiro (Universitas Islam Negeri Walisongo Semarang, 2019)
As ESP teachers, the teachers are always forced to maintain their knowledge because the development of specific knowledge is changing very fast. The teachers should progressively develop their competence because it will influence the goal of teaching (Latha, 2014). This study focuses on investigating the kinds of challenges that have faced by vocational teachers in developing their professional competence. The research design of this study is a case study. The participants of this study were five vocational teachers who have been teaching in Vocational Schools in Indramayu at least for about two years. The writer used a semi-structured interview to collect the data. The data from the meeting were transcribed and analyzed qualitatively. The result showed that there are three main challenges in developing professional competence. Those challenges are the availability of seminars and workshops in their city, the less support from the institution, and the lack of facilities and infrastructure.